Field-induced dielectric response saturation in o-TaS3. (3rd August 2016) - Ma, Yongchang; Lu, Cuimin; Wang, Xuewei; Du, Xueli; Li, Lijun; Petrovic, Cedomir
Abstract: We investigated dependence of the dielectric properties on temperature and electric field below 50 K along the chain direction of o -TaS3 . With external electric field increase, two threshold features could be identified. For electric fields somewhat larger than the lower threshold E T ′, the dielectric constant starts to decrease whereas the conductivity increases due to the tunnelling of solitons. For higher external electric field we observe a saturation of dielectric response and analyze that the possible reasons may be related to the polarization behavior of charged solitons. With a decrease in temperature, the effect of external field on the dielectric response of the system weakens gradually and at 13 K it diminishes due to soliton freezing.